The Use of Slang in Delivering Social Satires: A Sociolinguistic Study of Kurtis Conner's YouTube Content - Rizkya Halimatus Sya'diah; Otong Setiawan Djuharie (CV. Kalimasada Group Profesional, 2025)
This study aims to reveal how slang is used as a satirical tool in delivering social criticism through Kurtis Conner's YouTube content. The focus of the study lies on ironic, hyperbolic, and parodical linguistic forms, and how these elements shape social messages in the digital space. This research uses a qualitative approach with a sociolinguistic discourse analysis method. Data were collected through direct observation and transcription of five Kurtis Conner videos containing satirical elements and the use of slang. The results show that the use of slang in the content not only reflects the communication style of young people, but also serves as a means of delivering social criticism in a subtle but effective manner. Through humor, irony, and satire, slang is able to voice dissatisfaction with conservative values, shallow popular culture, and other social biases. This study concludes that slang in digital media has an important role in shaping young people's social awareness through satirical strategies.